New orthotopic implantation model of human esophageal squamous cell carcinoma in athymic nude mice - Song, Shuai (Thorac Cancer, 2014)
BACKGROUND: Subcutaneous xenograft is a common method to establish animal models of human esophageal squamous cell carcinoma (ESCC). However, the growth microenvironment of transplanted tumors is different from primary tumors. Orthotopic implantation models can provide more biologically relevant context in which to study the disease. So far, an orthotopic implantation model of ESCC has rarely been reported. METHODS: The human ESCC cell line KYSE30 was transfected with pLVX-Luciferase plasmids. KYSE30-Luciferase cells were isolated and injected into the flanks of nude mice to develop a subcutaneous tumor. An orthotopic implantation model was established using the fragments derived from the subcutaneous tumor. Fluorescence imaging was used to observe the development of the orthotopic implanted tumor. Hematoxylin and eosin staining was performed to evaluate the invasion and metastasis of the tumor. RESULTS: KYSE30 cells were successfully transfected with pLVX-Luciferase plasmids. A primary tumor was developed in all mice. The mice experienced body weight loss. The implanted tumor infiltrated into the esophageal muscularis propria. However, neither distant organ nor lymph node metastasis was found. The progression of the primary tumor was monitored by in vivo fluorescence imaging. CONCLUSION: The orthotopic implantation model can be established by sewing the fragments of human ESCC to the abdominal esophagus of a nude mouse. The progression of an orthotopic implantation tumor can be monitored in real time by in vivo fluorescence imaging.